Chasing shadows : my life tracking the great white shark - Skomal, Gregory; Talbot, Ret (William Morrow, an Imprint of HarperCollins Publishers, 2023)
"As shark attacks continue to rise along the coast of New England, Dr. Greg Skomal, the leading great white shark expert in the country, takes readers on a gripping exploration of these apex predators and the factors in their resurgence"--